Creative Districts and Creative Tourism - Piqué, Jorge; Richards, Greg (Diálogo com a Economia Criativa, 2022)
This paper presents a conversation between Greg Richards and Jorge Piqué on the development of creative districts and their links to creative tourism. The discussion ranged from the genesis of creative districts and creative tourism to contemporary challenges of creative placemaking. It includes a consideration of the development of cultural tourism, and how creative tourism emerged as a separate field of analysis in the new Millennium. As places have sought to distinguish themselves in an increasingly competitive global market, they have turned to creativity as a source of inspiration. Tourists tired of standardised products and crowded cultural sites have sought out the more localised experiences provided by creative districts and creative tourism. Creative districts have therefore become a vital tool for placemaking, providing access to the ‘extraordinary everyday’ and generating new models of creative tourism.